Anti-hyperplasia Effects of Total Saponins From Phytolaccae Radix in Rats With Mammary Gland Hyperplasia via Inhibition of Proliferation and Induction of Apoptosis - Li, Xiaoliang; Wang, Zhibin; Wang, Yu; Zhang, Yanan; Lei, Xia; Xin, Ping; Fu, Xin; Gao, Ning; Sun, Yanping; Wang, Yanhong; Yang, Bingyou; Wang, Qiuhong; et al. (Frontiers in Pharmacology, 2018)
Mammary gland hyperplasia (MGH) is a pathological condition that affects the majority of women at the child-bearing stage. The hormone and endocrinal therapy are typically used to treat MGH. Nevertheless, there are still some certain side effects accompanied with the benefits, which negatively affect the life quality of patients. Therefore, plant-derived agents that are effective against MGH development and with fewer side effects should be developed. The aim of this study was to investigate the protective effects and underlying mechanism of total saponins of Phytolaccae (TSP) against MGH in vivo. The results showed that treatment with TSP could significantly correct the disorder of serum sex hormones levels in rats with MGH, and eliminate the formation of MGH. Moreover, TSP significantly protected estrogen & progesterone-induced MGH histological changes, inhibited the swelling of the nipple, and improved the organ coefficient of uterus in rats with MGH. Mechanistically, TSP treatment not only effectively suppressed the mRNA and protein expression of ERα and PR in mammary gland, but also simultaneously up-regulated ERβ expression, and thus blocked sex hormones from interacting with their receptors. TSP treatment markedly suppressed mammary phosphorylation levels of ERK1/2, as well as reduced the mRNA and protein overexpression of VEGF and bFGF in mammary of rats. In addition, TSP treatment substantially down-regulated the expression of Bcl-2 and Ki-67, as well as elevated the expression of Bax. These findings indicated that TSP could potentially be used for effective treatment of MGH.